Prospects of Protected Vegetable Cultivation Technologies in Punjab - Kamalpreet Kaur, Prabhjot Kaur, Ravinder Kaur Dhaliwal and Kulbir Singh, (Indian Journal of Extension Education, 2018)
A survey was undertaken to study the prospects of protected vegetable cultivation technologies in Punjab covering sixdistricts viz. Amritsar, Gurdaspur, Sangrur, Moga, Jalandhar and Kapurthala. From these districts a total of 150respondents were selected for the purpose of study by probability proportion of protected vegetable cultivation growers inthe selected districts. Data were collected by personal interview method. The prospects and satisfaction of the protectedvegetable growers were studied. Questions were asked from the farmers regarding the prospects of protected vegetablecultivation. The results reveal that protected cultivation of vegetable gained importance since 2009 in Punjab becausemajority of respondents adopt this technique during 2009-2013. The data further showed that 34.48 per cent ofrespondents were willing to increase the area under protected vegetable cultivation due to profitable enterprise. Whilemaximum number of respondents (45.98%) wanted to keep the area constant under protected vegetable cultivationtechnologies due to non availability of land to increase the area and unable to handle protected structures on more area.Majority of respondents preferred poly house followed by net house for cultivation of vegetables and maximum numberof respondents were satisfied from this technology. It may be concluded that it is a profitable enterprise for farmers due tooff season production and high yield so maximum number of respondents were willing to keep the area constant orincrease the area under protected structures for vegetable cultivation.